Immune Status and Growth of Broiler Fed Diet with Microparticle Protein Added with Natural Acidifier - Suthama, N.; Sukamto, B.; Mangisah, I.; Krismiyanto, L. (Tropical Animal Science Journal, 2021)
The present study was conducted to evaluate the feeding effect of diet composed of microparticle protein added with lime juice as an acidifier on immune status and efficiency of protein utilization in relation to the growth of broiler chicken. Dietary treatments tested were P1 was diet with 20% intact protein and CaCO3 as a Ca source, P2 was diet with 20% microparticle protein and eggshell as a Ca source added with 1.2% lime juice, and P3 was diet with 20% microparticle protein and eggshell as a Ca source added with 2.4% lime juice. Variables measured were protein and amino acids digestibility, retentions of N and Ca, fecal Nτ–methyl histidine (Nτ–MH) excretion as a protein turnover index, lymphoid organs, heterophil and lymphocyte (H/L) ratio, immunoglobulin A (IgA) as a body resistance indicator, feed consumption, body weight gain (BWG), and feed conversion ratio (FCR). The experiment was arranged in a completely randomized design with 3 treatments and 8 replications. Data were subjected to analysis of variance and Duncan test at 5% probability. Protein and amino acid digestibility, N, and Ca retentions were significantly (p<0.05) higher in P2 and P3. However, the H/L ratio was significantly (p<0.05) lower in both treatments compared to P1. Bursa fabricius and lymph weights were not difference, but BWG in P2 significantly (p<0.05) increased. In conclusion, protein and some essential amino acids digestibility, N and Ca retentions, IgA, and BWG increase with the decrease in H/L ratio, fecal Nτ–MH, feed consumption, and FCR in broiler fed diet composed of microparticle protein source with additional 1.2 mL acidifier of lime juice.